Current position of beta-adrenoblockers in coronary heart disease management: information for clinicians - I. A. Libov; Yu. N. Moiseeva; A. R. Gaynullina (Кардиоваскулярная терапия и профилактика)
Beta-adrenoblockers (ВАВ) are widely used in coronary heart disease (CHD) management. The choice of specific ВАВ and their place in optimal schemes for CHD treatment are discussed.